Pictorama: Text based Image Editing using Diffusion Model - Vishal Mamluskar, Allen Lopes, Nesan Selvan, Teena Varma, Harshali Patil, Kavita Jain, Deepali Vora, Akash Sawant (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research aims to pioneer image modification through text, integrating natural language descriptions with advanced computer vision and NLP techniques. The primary objective is to bridge human language and image editing, empowering users to convey creative visions effortlessly, revolutionizing the field of image modification. The study employs stable diffusion models, leveraging PyTorch and Python. It builds on prior works like Imagic, LEDITS, and Instructpix2pix, integrating a novel Vector Quantized Diffusion (VQ-Diffusion) model. The model is trained on a dataset of 436 GB containing 3 features an input image, an editing instruction, and an output edited image. Test samples include real images subjected to diverse text prompts for image edits, with disentanglement properties explored. The approach combines text inversion and Box-Constrained Diffusion (BoxDiff) for personalized and conditional image synthesis. The research showcases that stable diffusion models exhibit disentanglement properties, enabling effective modifications without extensive fine-tuning. The introduced BoxDiff and VQ-Diffusion models demonstrate superior performance in spatially constrained and complex scene synthesis, outperforming traditional methods. We are able to observe greater quality in output images with good cohesiveness throughout the image. Runing the model with greater number of steps allows for upheaval in quality. Here we have used 100 steps for greater image quality. The effect of number of steps on the time taken for inference is also studied. Due to the large amount of video memory required for inferencing, we recommend a GPU with >11 GB of video memory. The study adds value by addressing biases, achieving higher speeds, and enhancing image quality, contributing to the evolving landscape of text-to-image synthesis. This research introduces novel approaches in disentanglement, spatially constrained synthesis, and rapid image generation, pushing the boundaries of text-to-image synthesis beyond existing limitations.